A Production systems study on Gomeco Metal Corporation - Castro, Carlo Alfred S. (College of Engineering, 1996)
Gomeco Metal Corporation is classified as a large-scale manufacturer of various stainless steel, food service kitchen equipment. As it caters to its very wide array of clients, it often encounters problems in areas of manpower, materials, management, and methods. Systems Analysis, however, revealed that the root of Gomeco's major problems, is the Lack of a Production Management System. A production Plan was therefore proposed to address the situation.